2015
DOI: 10.1111/acel.12415
|View full text |Cite
|
Sign up to set email alerts
|

Central insulin‐like growth factor‐1 ( IGF ‐1) restores whole‐body insulin action in a model of age‐related insulin resistance and IGF ‐1 decline

Abstract: SummaryLow insulin‐like growth factor‐1 (IGF‐1) signaling is associated with improved longevity, but is paradoxically linked with several age‐related diseases in humans. Insulin‐like growth factor‐1 has proven to be particularly beneficial to the brain, where it confers protection against features of neuronal and cognitive decline. While aging is characterized by central insulin resistance in the face of hyperinsulinemia, the somatotropic axis markedly declines in older humans. Thus, we hypothesized that incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 39 publications
1
45
0
2
Order By: Relevance
“…PRDX-3 is mainly responsible for the detoxification of 90% of the hydrogen peroxide in the mitochondria (23). By contrast, low IGF-1 signaling is closely associated with improved longevity (24). As aforementioned, QEF improved impaired memory of D-galactose-treated mice, therefore, the expression levels of these genes or their products in hippocampus were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…PRDX-3 is mainly responsible for the detoxification of 90% of the hydrogen peroxide in the mitochondria (23). By contrast, low IGF-1 signaling is closely associated with improved longevity (24). As aforementioned, QEF improved impaired memory of D-galactose-treated mice, therefore, the expression levels of these genes or their products in hippocampus were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Energy expenditure, substrate utilization and spontaneous activity were determined by indirect calorimetry as described (Huffman et al, 2016; Huffman et al, 2007), based upon O 2 consumption and CO 2 production, using a Rat Oxymax System (Columbus Instruments, Columbus, OH). In brief, YAL and OAL and DR animals (n = 8 per group) were placed into individual cages and allowed to acclimate for at least 72 hr prior to the experiment.…”
Section: Star⋆methodsmentioning
confidence: 99%
“…In addition, plasma sarcosine levels were evaluated in venous blood collected from an indwelling catheter at several time points to characterize levels throughout the day, as well as under fed and fasted conditions, in 4–5 mo old FBN male rats. Specifically, animals were sedated with 2% isoflurane for surgical placement of an indwelling catheter into the right internal jugular vein, similar as described (Huffman et al, 2016). Rats were then singly housed and treated with analgesic as needed and monitored until body weight returned to within 3% of preoperative levels (~7 days).…”
Section: Star⋆methodsmentioning
confidence: 99%
“…Furthermore, IGF-1R and InsR can combine to form heterodimers known as IGF-1R/InsR hybrids, and the expression of these hybrid receptors can account for a significant proportion of total receptor stoichiometry in some tissues, including heart, muscle and brain (Bailyes et al, 1997). Physiologically, IGF-1 has been shown to have similar effects as insulin both in the periphery (Hawkins et al, 1996) and in the brain (Muzumdar et al, 2006) to regulate glucose homeostasis, though centrally-acting IGF-1 proved more potent than insulin in regulating peripheral glucose fluxes in aging (Huffman et al, 2016). …”
Section: Gh/igf-1 Axis and Age-related Diseasesmentioning
confidence: 99%
“…Studies in rodents focused on the IGF-1 axis have been most well studied, and have revealed that IGF-1 levels in circulation, CSF and brain tissue decline with advancing age in some strains, while expression of the IGF-1R in various regions of the CNS either increases, decreases, or remains unchanged (Ashpole et al, 2015; Huffman et al, 2016). Evidence regarding the role of local GH and IGF-1 in cognition is limited, but expression of GH and IGF-1 in the hippocampus of dwarf mice was found to be paradoxically increased, suggesting that maintenance of adequate IGF-1 levels in the brain may be critical to normal cognitive function in these mice (Sun et al, 2005).…”
Section: Gh/igf-1 Axis and Age-related Diseasesmentioning
confidence: 99%